La importancia de la reversión a ritmo sinusal en la fisiopatología de la fibrilación auricular: un abordaje desde la perspectiva básico-clínica - Parra L., Alfredo; Varela L., Diego (Revista Hospital Clínico Universidad de Chile, 2025)
Atrial Fibrillation (AF) represents a major global public health concern, with its prevalence projected to rise in the coming years primarily due to population aging — the principal risk factor associated with the condition. AF imposes a substantial economic burden on healthcare systems and is linked to elevated morbidity and mortality rates. Numerous studies have underscored the clinical relevance of achieving early restoration of sinus rhythm in patients with AF, as prolonged periods of irregular atrial activity are associated with adverse hemodynamic and thromboembolic consequences. Nevertheless, atrial rhythm irregularity is not the sole defining feature of AF. The progressive electrical and structural remodeling that characterizes the natural history of this arrhythmia drives its evolution from paroxysmal AF toward long-standing persistent and ultimately permanent AF. The term “permanent AF” reflects, more than the duration of the arrhythmia, a therapeutic decision to forego further attempts at rhythm control, given that advanced atrial remodeling often renders cardioversion ineffective. Multiple strategies have been employed to restore and maintain sinus rhythm, including pharmacologic suppression of aberrant electrical activity, modulation of the cellular action potential, and disruption of micro–reentrant circuits through physical or ablative interventions. Each approach exhibits variable efficacy and carries specific risks of adverse effects. Despite significant therapeutic advances, ongoing research is warranted to develop novel and more individualized management strategies for AF, enabling tailored interventions based on the underlying pathophysiologic substrate and patient profile.